Motrices expressions: approaches theoretical-epistemological houghts about the curriculum of the degree of physical education and sports of University of the Llanos (Impetus, 2021)
Product of discussions for more than five years are around the program Degree of Physical Education and Sports of the University of the Llanos, during their curricular restructuring, it becomes imperative to generate some reflections preliminarily be set up on platform on which dynamically allow sustained dialogue of knowledge and expertise to help strengthen the academic and training program development, but also as part of an exercise of self-regulation on their doing, their work, their responsibility to the context and presence in the region of the Colombian Orinoquia, proposing to local and regional community serious introspection about the shortcomings and belongings of the disciplinary field of physical education. This, as will be the case here try to expose, part specifically one of the core components of the proposed curriculum, called motor expressions, as a possibility to understand that live there nonexclusive body modes deployment of sports, recreation or physical education in schools, but a motor skills a long list of other likely to be incorporated in the new curriculum bet LEFyD Unillanos Program.